2019
DOI: 10.12890/2019_001094
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Adult Acute Disseminated Encephalomyelitis Associated with Primary Epstein-Barr Virus Infection

Abstract: We report a rare case of acute disseminated encephalomyelitis (ADEM) secondary to a primary Epstein-Barr (EBV) infection, in a 22-year-old male. Symptomatic infectious mononucleosis and ADEM are both quite uncommon conditions in this age group. LEARNING POINTS ADEM is a very rare CNS disorder; it is more common in childhood but can also be described in adults. The clinical evaluation must focus on the presence of recent signs of infection or vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…EBV infection is mostly asymptomatic in healthy individuals, but a small number can develop CNS complications including demyelinating disease, acute encephalitis, acute cerebellar ataxia, meningitis, or myelitis [8]. A few cases of EBV infection-related ADEM have been reported (Table 1 [8][9][10][11][12][13][14]).…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection is mostly asymptomatic in healthy individuals, but a small number can develop CNS complications including demyelinating disease, acute encephalitis, acute cerebellar ataxia, meningitis, or myelitis [8]. A few cases of EBV infection-related ADEM have been reported (Table 1 [8][9][10][11][12][13][14]).…”
Section: Discussionmentioning
confidence: 99%
“…This case report highlights the importance of considering the possibility of a broad spectrum of causes for neuropsychiatric manifestations in a patient with SLE. And in a patient with presumptive diagnosis of TTP and neurological manifestations who does not show an adequate response to TPE, an alternative or superadded aetiology for his/her neurological manifestations [9,10] should be thought of and investigated for. Lastly, it should be noted that prompt administration of more potent immunosuppressive therapy beyond the standard treatment in ADEM occurring in a background of an autoimmune condition like SLE, can be life saving like in the case of this young patient.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features include acute onset, multifocal neurological deficits with a monophasic course, and a typical clinical course of rapid neurological deterioration over several days. Most patients have viral prodromal symptoms followed by the development of focal neurological deficits and a good prognosis after symptomatic treatment, although some cases experience severe complications and mortality ( Bahadori et al, 2007 ; Phowthongkum et al, 2007 ; Di Carlo et al, 2011 ; Ali et al, 2019 ).…”
Section: Ebv and Acute Disseminated Encephalomyelitismentioning
confidence: 99%
“…EBV can cause encephalopathy directly in the CNS or indirectly via autoimmune ADEM( Wong et al, 1999 ; Bahadori et al, 2007 ). The immune-mediated process of EBV-related acute disseminated encephalitis and infected encephalomyelitis can lead to the multifocal demyelination of peripheral venous white matter, positive EBV IgM in CSF, and positive EBV DNA in the serum ( Saeed et al, 2014 ; Ali et al, 2019 ). One study found cross-reactivity between EBNA-1 and myelin oligodendrocyte glycoprotein (MOG), in which EBV infection triggered the production of anti-MOG antibodies thereby elevating MOG concentrations and inducing the development of ADEM ( Selter et al, 2010 ; Lalive et al, 2011 ; Nakamura et al, 2017 ).…”
Section: Ebv and Acute Disseminated Encephalomyelitismentioning
confidence: 99%